2013
DOI: 10.4028/www.scientific.net/amm.390.478
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Design for the Transfer from the Lissajous Orbit of Sun-Earth System to Asteroids

Abstract: This paper investigates the trajectory design issue for the transfer from the Lissajous orbit of CHANGE 2 probe to asteroids. First, an intersection search method, which is a general design method of low-energy transfer trajectories by searching the intersection of unstable and stable manifolds in the circular restricted three-body problem (CRTBP), is applied to produce the zero-cost flyby trajectories for the asteroid flyby missions of CHANGE 2 probe, and the simulation result shows that this method is invali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…We also calculated the transfers for 2010 JK1 asteroid (Wang et al, 2013), and observed the similar phenomenon, i.e., the transfer opportunities are divided into separate families and close to the ecliptic plane.…”
Section: Why Two Separate Transfer Families Are Existedmentioning
confidence: 98%
See 1 more Smart Citation
“…We also calculated the transfers for 2010 JK1 asteroid (Wang et al, 2013), and observed the similar phenomenon, i.e., the transfer opportunities are divided into separate families and close to the ecliptic plane.…”
Section: Why Two Separate Transfer Families Are Existedmentioning
confidence: 98%
“…For the design of transfer trajectory of the CE-2's asteroid flyby mission, Qiao et al (2013b) proposed a perturbation method, which generated the transfer by correcting the initial guess that is obtained by performing a velocity perturbation in the direction of unstable eigenvector of LPO, to calculate the transfer opportunities and design the actual trajectory for CE-2. Wang et al (2013) used the similar procedure to search the possible flyby opportunities for the asteroids Toutatis and 2010 JK1. Gao (2013) presented the modified unstable manifolds and the grid search method to find the unconstrained two-impulse asteroid flyby trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer from lunar orbit to asteroid is usually considered as an extended mission for lunar probe, such as the Clementine of NASA [5]. Recently, Chinese lunar probe, Chang'e-2 (CE-2), had successfully finished an extended mission, i.e., orbiting the Sun-Earth L2 and flyby Toutatis asteroid [6][7][8][9][10][11][12]. By implementing extended mission, the probe could achieve maximum exploitation and receive additional scientific return.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ballistic capture mechanics in the restricted three-body problem, transfers between NEAs and LPOs have also been investigated in recent years (Yá rnoz et al 2013;Mingotti et al 2014a;Farquhar et al 2004;Zimmer 2013;Wang et al 2013;Gao 2013). For example, Mingotti et al (2014a) proposed the use of low thrust propulsion to capture NEAs to a target periodic orbit around the Sun-Earth L1 and L2 points by using the stable manifolds associated with the target periodic orbit.…”
Section: Introductionmentioning
confidence: 99%
“…In order to lower the cost of space exploration missions, Zimmer (2013) studied reusability by stationing spacecraft on periodic orbits at the Sun-Earth L1 and L2 points between NEA missions. In related work, a differential correction method was proposed to design flyby trajectories from a 4 Lissajous orbit of the CHANG'E 2 spacecraft to the asteroids Toutatis and 2010 JK1 (Wang et al 2013). …”
Section: Introductionmentioning
confidence: 99%